Kampung Style Restaurant - Omar, Aniqah Aimi Shazwani; Rajeli, Nurfarahin; Jasuli, Nuraina Jasslyza; Fardiansyah, Fazrien; Judin, Muhammad Aizat (2013)
The name of our company is Kampung Style Restaurant. As we all know, there is not many restaurant or food court that serve Sabah's traditional food, whereby our restaurant serve variety of delicious and nutritious traditional food from many cultures. Our restaurant likes to fulfil people's craving for home cook taste that surely make them come again. Therefore, our restaurant will be the only restaurant that serves various traditional foods in one place. Kampung Style Restaurant is located at Jesselton Point. Jesselton Point is strategic place for our restaurant because it is the centre of the city and one of the attractions where it is a checkpoint for tourist to go to islands and for local people to chill and hangout with beautiful view at night. In addition, Kampung Style is located near the raw material and supplier. Kampung Style is a new business for us, therefore we have to find suitable price of rental that located at strategic place which is why we choose Jesselton Point. Our target market is all people around Sabah, local people and tourists are all welcome. Our potential prospect is local people who leave their hometown for work. The reason why we choose them as our target is because nowadays it is hard for the employees either from public sector or private sector to have leaved more than 3 days. So it is hard for them to go back to their hometown, to have delicious traditional food. Another reason is, children nowadays are quite choosy when it come to foods that their seldom eat. It is hard for them when they follow their parents go back to their hometown and here, we are serving traditional food for parents to bring their children to enjoy traditional food. Those are the purpose of Kampung Style which is to fulfil people's craving for home cook and introduce to the children traditional food in Sabah. Last but not least, our target market is the tourists. The reason is we want to promote Sabah's Traditional food in national worldwide.